2003
DOI: 10.1016/s0091-6749(03)00018-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial DNA in House and Farm Barn Dust

Abstract: Background: Early in life, natural exposure to microbial components (eg, endotoxin) may mitigate allergy and asthma development in childhood. Bacterial DNA is a potent stimulus for the innate immune system; its immune stimulatory potential in dust is unknown. Objectives: We sought to quantify bacterial DNA and endotoxin content in dust from urban homes, rural homes, farm homes, and farm barns and to determine if dust DNA is immune-stimulatory. Methods: Total DNA, bacterial DNA, and endotoxin were measured in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
1
27
0
1
Order By: Relevance
“…The LPS concentration that we used in the current studies is in line with other in vitro progenitor cell studies, which have found minimal progenitor cell responses to LPS below 10 μg/ml. In addition, Roy et al . have demonstrated that endotoxin levels range between 1 and 6 μg/g house dust in rural and urban homes.…”
Section: Discussionmentioning
confidence: 99%
“…The LPS concentration that we used in the current studies is in line with other in vitro progenitor cell studies, which have found minimal progenitor cell responses to LPS below 10 μg/ml. In addition, Roy et al . have demonstrated that endotoxin levels range between 1 and 6 μg/g house dust in rural and urban homes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for the lack of association between microbial markers and atopic outcomes. It is possible that other microbial factors, such as bacterial DNA [41], mediate the protective benefit of dog exposure on the development of atopic disease. In addition, perhaps airborne dust sampling or other technologies could provide more accurate indices of personal exposure to allergens or innate immune stimuli, and studies involving these technologies could yield additional information related to effects on immune development.…”
Section: Discussionmentioning
confidence: 99%
“…human, animal) DNA via TLR9, and bacterial cell wall components other than endotoxin are recognised by TLR2. Exposure to bacterial DNA and TLR2 ligands also appears to vary, in levels that correlate yet are distinct from endotoxin 30,31 . These ligands also interact and alter the cellular and immune responses to endotoxin.…”
Section: Health – Disease Determinants Exemplified By Bacterial Endotmentioning
confidence: 99%